Taxonomic review of Kuzicus Gorochov, 1993 (Tettigoniidae: Meconematinae), with two new species from Thailand and key to species - Tan, Ming Kai; Dawwrueng, Pattarawich; Artchawakom, Taksin (Zootaxa, 2015)
The taxonomy of genus Kuzicus Gorochov, 1993 (Tettigoniidae: Meconematinae) is reviewed. Two new species are described from Thailand: Kuzicus pakthongchai sp. n. Tan et al. and Kuzicus multidenticulatus sp. n. Tan et al. Kuzicus denticuloides (Kevan, 1993) comb. nov. is transferred from genus Xiphidiopsis. Parakuzicus is removed as a subgenus and considered a distinct genus. A key to species of Kuzicus is provided.